2020
DOI: 10.3390/nu12051299
|View full text |Cite
|
Sign up to set email alerts
|

Leucine Supplementation: A Novel Strategy for Modulating Lipid Metabolism and Energy Homeostasis

Abstract: Lipid metabolism is an important and complex biochemical process involved in the storage of energy and maintenance of normal biological functions. Leucine, a branched amino acid, has anti-obesity effects on glucose tolerance, lipid metabolism, and insulin sensitivity. Leucine also modulates mitochondrial dysfunction, representing a new strategy to target aging, neurodegenerative disease, obesity, diabetes, and cardiovascular disease. Although various studies have been carried out, much uncertainty still exists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 142 publications
3
33
0
Order By: Relevance
“…In agreement with reports across numerous studies illustrating the positive effect of Leucine on insulin sensitivity ( Zhang et al, 2020 ), our data herein suggests that certain amino acid metabolites may also have the ability to positively modulate glucose metabolism under specific conditions. One potential mechanism that may underlie any improvement in insulin sensitivity could be an increase in leg blood flow facilitating greater peripheral glucose uptake, however this increase was not evident in this study.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with reports across numerous studies illustrating the positive effect of Leucine on insulin sensitivity ( Zhang et al, 2020 ), our data herein suggests that certain amino acid metabolites may also have the ability to positively modulate glucose metabolism under specific conditions. One potential mechanism that may underlie any improvement in insulin sensitivity could be an increase in leg blood flow facilitating greater peripheral glucose uptake, however this increase was not evident in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Leucine functions as a direct-acting nutrient signal in WAT to affect lipid metabolism, thus favoring adiposity reduction (Yao et al, 2016;Zhang et al, 2020). Despite these positive outcomes, multiple lines of evidence have pointed out that elevated levels of circulating leucine may precede or coincide with insulin resistance and cardiovascular dysfunction, thus seriously threatening human health (Felig et al, 1969;Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolic activity of the gut microbiota can be linked to host body energy homoeostasis by short-chain fatty acids (SCFAs), which are produced by gut microbiota catabolizing dietary fibers (Topping and Clifton, 2001). There is compelling evidence that nutrients can attenuate obesity by reprogramming gut microbiota (Xu et al, 2017;Yin et al, 2018;Zhang et al, 2019;Wang et al, 2020;Zhong et al, 2020). Using a rodent model, we also found that HMB could mitigate lipid metabolism disorders by reprogramming gut microbiota, as manifested by the increased ratio of Bacteroidetes to Firmicutes and elevated Bacteroidetesproduced propionic acid (Duan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Function of GLP-1 and GIP is compromised in T2D, but research suggests BCAA ingestion stimulates inhibited GLP-1 and GIP for improved insulin secretion [ 203 , 204 , 206 ]. Special consideration has been given to leucine and its metabolites due to its insulinotropic effects and stimulation of the mammalian target of rapamycin (mTOR) pathway which regulates protein synthesis, cell growth, and fuel metabolism [ 203 , 207 , 208 , 209 ]. Specifically, rapamycin-sensitive (mTORC1), a component of mTOR, is activated in response to an increase in cellular levels of leucine [ 209 , 210 ].…”
Section: Potential Supplements For Type 2 Diabetesmentioning
confidence: 99%
“…Special consideration has been given to leucine and its metabolites due to its insulinotropic effects and stimulation of the mammalian target of rapamycin (mTOR) pathway which regulates protein synthesis, cell growth, and fuel metabolism [ 203 , 207 , 208 , 209 ]. Specifically, rapamycin-sensitive (mTORC1), a component of mTOR, is activated in response to an increase in cellular levels of leucine [ 209 , 210 ]. This signaling pathway elicits mRNA translation and protein synthesis while decreasing muscle wasting and cell death when activated [ 208 , 211 ].…”
Section: Potential Supplements For Type 2 Diabetesmentioning
confidence: 99%